Pemanfaatan Batu Sungai Leoran Kecamatan Cendana Kabupaten Enrekang Sulawesi Selatan Pada AC-WC - Tomi Kanallo; Rais Rachman; Alpius (Paulus Civil Engineering Journal, 2022)
This study aims to determine the characteristics of the material, the composition of the AC-WC mixture, the use of the AC-WC mixture, and determine the IKS value of the stone of Sungai Leoran, Pinang Village. Testing the characteristics of aggregate, asphalt, and filler then designing LASTON AC-WC followed by conventional Marshall testing and Marshall Immersion testing is the method used. The results of this study indicate that the material from the Leoran River meets the specification standards in road pavement work. The composition used for the AC-WC mixture is 36.75%, fine aggregate 50%, filler 5.75%, with KAO of 7.50%. The Residual Strength Index is 96.57% with a KAO of 7.50%. The results of the study meet the standard specifications, namely obtaining a Residual Strength Index value of 96.57% with an OAC of 7.50%.